“It Takes a Village to Raise a Child”: Early Child Development in Relation to Other Social Determinants of Health - Zaman, Urooj (Revue YOUR Review (York Online Undergraduate Research), 2017)
This project examines early childhood development in light of other key social determinants of health. A literature review of secondary sources shows that the social determinants of health are interrelated, and are shaped by broader social and local spheres—family, place of residence, and workplace. Of the fourteen social determinants of health, early child development is crucial because it influences adult health and involves irreversible changes, such as those brought about by mental or physical damage to the fetus, and the development of mental capacity by age two. Moreover, early child development is distinguished from other social determinants of health as it holds greater promise for change. While eradicating poverty at any life stage is difficult, minimizing the effects of poverty may be easiest during early childhood. This is because children interact with both the broader social and the local family spheres, allowing them to engage in other positive environments, even if their own parents are victims of poverty. Thus, health policy should prioritize early child development because it may contribute to ending the cycle of poverty.